Recombination in Streptococcus pneumoniae Lineages Increase with Carriage Duration and Size of the Polysaccharide Capsule - Chrispin Chaguza (American Society for Microbiology, 2016)
ABSTRACT Streptococcus pneumoniae causes a high burden of invasive pneumococcal disease (IPD) globally, especially in children from resource-poor settings. Like many bacteria, the pneumococcus can import DNA from other strains or even species by transformation and homologous recombination, which has allowed the pneumococcus to evade clinical interventions such as antibiotics and pneumococcal conjugate vaccines (PCVs). Pneumococci are enclosed in a complex polysaccharide capsule that determines the serotype; the capsule varies in size and is associated with properties including carriage prevalence and virulence. We determined and quantified the association between capsule and recombination events using genomic data from a diverse collection of serotypes sampled in Malawi. We determined both the amount of variation introduced by recombination relative to mutation (the relative rate) and how many individual recombination events occur per isolate (the frequency). Using univariate analyses, we found an association between both recombination measures and multiple factors associated with the capsule, including duration and prevalence of carriage. Because many capsular factors are correlated, we used multivariate analysis to correct for collinearity. Capsule size and carriage duration remained positively associated with recombination, although with a reduced P value, and this effect may be mediated through some unassayed additional property associated with larger capsules. This work describes an important impact of serotype on recombination that has been previously overlooked. While the details of how this effect is achieved remain to be determined, it may have important consequences for the serotype-specific response to vaccines and other interventions. IMPORTANCE The capsule determines >90 different pneumococcal serotypes, which vary in capsule size, virulence, duration, and prevalence of carriage. Current serotype-specific vaccines elicit anticapsule antibodies. Pneumococcus can take up exogenous DNA by transformation and insert it into its chromosome by homologous recombination. This mechanism has disseminated drug resistance and generated vaccine escape variants. It is hence crucial to pneumococcal evolutionary response to interventions, but there has been no systematic study quantifying whether serotypes vary in recombination and whether this is associated with serotype-specific properties such as capsule size or carriage duration. Larger capsules could physically inhibit DNA uptake, or given the longer carriage duration for larger capsules, this may promote recombination. We find that recombination varies among capsules and is associated with capsule size, carriage duration, and carriage prevalence and negatively associated with invasiveness. The consequence of this work is that serotypes with different capsules may respond differently to selective pressures like vaccines.